2021
DOI: 10.1159/000518206
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Languages and Cultural Backgrounds on Voice Quality Analyses

Abstract: <b><i>Objective:</i></b> The aim of this study was to verify the influence of different cultural backgrounds and languages on the perception of voice quality. Another aim was to evaluate the correlation between clinical auditory-perceptual judgments with acoustic measurements, such as the acoustic voice quality index (AVQI) and the acoustic breathiness index (ABI), i.e., their effect on the concurrent validity. <b><i>Methods:</i></b> Brazilian and European partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…2). Its threshold varies between AVQI versions [18,19] and languages/cultural backgrounds [20] Age has minimal-to-no influence on the AVQI score (especially for younger adults), and sex has none [21,22]. Acceptable scores have been found for AVQI on voice assessment within the dysphonia classification of voice disorders (normal versus organic and functional voice disorders) [23] and a moderate to high correlation with self-perceived, questionnaire-based voice handicap of voiceimpaired patients has been found [24,25].…”
Section: Acoustic Voice Quality Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Its threshold varies between AVQI versions [18,19] and languages/cultural backgrounds [20] Age has minimal-to-no influence on the AVQI score (especially for younger adults), and sex has none [21,22]. Acceptable scores have been found for AVQI on voice assessment within the dysphonia classification of voice disorders (normal versus organic and functional voice disorders) [23] and a moderate to high correlation with self-perceived, questionnaire-based voice handicap of voiceimpaired patients has been found [24,25].…”
Section: Acoustic Voice Quality Indexmentioning
confidence: 99%
“…2). Its threshold varies between AVQI versions [18,19] and languages/cultural backgrounds [20]. It has high clinical utility and good results have been documented for diagnostic accuracy, concurrent validity and responsiveness to detect voice changes over time after different voice treatments (Y. Maryn, C. Batthyany, B. Barsties v. Latoszek, unpublished data).…”
Section: Acoustic Voice Quality Indexmentioning
confidence: 99%
“…Research on the effect of foreign language accent on auditory‐perceptual evaluations has focused on cross‐ language differences (e.g., an English speaker evaluating the voice of someone speaking Cantonese 14 ) rather than cross‐ accent differences. These studies found cross‐language differences in ratings of both global percepts of voice quality (e.g., overall severity of dysphonia) and individual percepts (e.g., strain) 14–16 . However, they do not address the question of whether accent differences within a language shared by speaker and listener would similarly affect auditory‐perceptual outcomes.…”
Section: Introductionmentioning
confidence: 95%
“…These studies found crosslanguage differences in ratings of both global percepts of voice quality (e.g., overall severity of dysphonia) and individual percepts (e.g., strain). [14][15][16] However, they do not address the question of whether accent differences within a language shared by speaker and listener would similarly affect auditory-perceptual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Voice quality metrics have been found to be useful and efficient in the analysis of a variety of very different spoken languages. The purpose of the [54] study was to confirm the impact of different cultural origins and languages (Brazil Portuguese and European Portuguese) on the perception of voice quality. Another goal was to evaluate the relationship between clinical auditory perception assessments and acoustic measures such as AVQI and ABI, as well as their influence on concurrent validity.…”
Section: Language Factors In Voice Quality Analysismentioning
confidence: 99%